Novel inhibitor cystine knot peptides from Momordica charantia. - Wen-Jun He (Public Library of Science (PLoS), 2013)
Two new peptides, MCh-1 and MCh-2, along with three known trypsin inhibitors (MCTI-I, MCTI-II and MCTI-III), were isolated from the seeds of the tropical vine Momordica charantia. The sequences of the peptides were determined using mass spectrometry and NMR spectroscopy. Using a strategy involving partial reduction and stepwise alkylation of the peptides, followed by enzymatic digestion and tandem mass spectrometry sequencing, the disulfide connectivity of MCh-1 was elucidated to be CysI-CysIV, CysII-CysV and CysIII-CysVI. The three-dimensional structures of MCh-1 and MCh-2 were determined using NMR spectroscopy and found to contain the inhibitor cystine knot (ICK) motif. The sequences of the novel peptides differ significantly from peptides previously isolated from this plant. Therefore, this study expands the known peptide diversity in M. charantia and the range of sequences that can be accommodated by the ICK motif. Furthermore, we show that a stable two-disulfide intermediate is involved in the oxidative folding of MCh-1. This disulfide intermediate is structurally homologous to the proposed ancestral fold of ICK peptides, and provides a possible pathway for the evolution of this structural motif, which is highly prevalent in nature.